Breast cancer knowledge, attitude and self-examination practices of physiotherapy students in India: a cross-sectional study - Parle, Jyoti; Gupta, Shivangi (International Journal Of Community Medicine And Public Health, 2020)
Background: Breast cancer is a major cause of cancer in Indian females. Breast self-examination (BSE) being a low-cost, effortless, and efficient procedure can help early detection in developing countries. Physiotherapists play an active role in community rehabilitation and this study aims to assess their knowledge about breast cancer, BSE as well as explore attitude and self-examination practice among physiotherapy students. Methods: This cross-sectional study was conducted among 380 students in various physiotherapy colleges of Navi Mumbai, using a pre-validated questionnaire. The data collected were analyzed using Statistical Package for the Social Sciences (SPSS) version 24. A chi-square test was applied to find an association between variables. Correlation analysis was used to test the strength of the relationship between numeric variables. Results: The study reported students had moderate knowledge about breast cancer (59.5%) and breast self-examination (BSE) (62.6%). Attitude towards self-examination practice was excellent (94.2%), but only (25.8%) of the respondents reported to perform BSE monthly. There was a significant association between the overall knowledge and practice of BSE (p=0.000). Also, a significant association was found between overall knowledge and attitude towards BSE (p=0.000). Conclusions: Health education strategies and awareness programs are necessary to keep in view the current status of breast cancer, BSE knowledge among health care professionals.